2014
DOI: 10.2147/copd.s58258
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with COPD newly prescribed a long-acting bronchodilator: a retrospective cohort study

Abstract: IntroductionThis study aimed to characterize patients with chronic obstructive pulmonary disease (COPD) newly prescribed a long-acting bronchodilator (LABD), and to assess changes in medication over 24 months.MethodsA cohort of patients with COPD aged ≥40 years newly prescribed an LABD between January 1, 2007 and December 31, 2009 were identified from the Truven Marketscan® Commercial Database (Truven Health Analytics, Ann Arbor, MI, USA) and followed for 24 months. Inclusion criteria included no prior prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 22 publications
5
23
0
2
Order By: Relevance
“…In our study, it was observed that within 2 years of initiating treatment for COPD, ICS therapy was added to 43% of patients on LABA or LAMA monotherapy, despite the low rate of exacerbations. This may reflect inappropriate initiation of ICS as previously described and is in line with the findings from other studies 16,17…”
Section: Discussionsupporting
confidence: 92%
“…In our study, it was observed that within 2 years of initiating treatment for COPD, ICS therapy was added to 43% of patients on LABA or LAMA monotherapy, despite the low rate of exacerbations. This may reflect inappropriate initiation of ICS as previously described and is in line with the findings from other studies 16,17…”
Section: Discussionsupporting
confidence: 92%
“…The overall finding of this study—that the prescribing of long‐acting bronchodilators and ICSs in patients with COPD does not appear to align with GOLD guidelines—is consistent with recent studies based on subgroups of patients in a variety of settings. Our observation that the most commonly dispensed first regimen involving a long‐acting bronchodilator was a LABA in combination with an ICS is consistent with findings from Spain, the Netherlands and some, but not all, studies based in the UK.…”
Section: Discussionsupporting
confidence: 83%
“…In several studies, researchers have had access to detailed clinical information which enabled them to assess the appropriateness of ICS use and subsequently conclude that ICS therapy was being overused . In line with our findings, previous investigations have also observed the use of ICS monotherapy in patients with COPD, including studies based on primary care databases in the UK and Spain, patients attending respiratory clinics in Italy, patients followed after discharge from hospital with a diagnosis of COPD in Italy and members of a health insurance database in the USA . Future studies may need to account for prescribing practices related to sub‐phenotypes of COPD, such as overlap syndromes, in which ICS may be prescribed at an earlier stage …”
Section: Discussionsupporting
confidence: 82%
“…Historically, use of and adherence to COPD maintenance medications has been suboptimal, with many individuals with COPD not receiving any maintenance medications (14,15,17). Among individuals who use COPD medications, adherence is low, which poses difficulties in medication management (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In this study, we found that only 22% of the sample achieved adherence of at least 80%, regardless of depression status.…”
Section: Original Researchmentioning
confidence: 64%
“…Maintenance medications, including inhaled corticosteroids, long-acting b-agonists, and long-acting anticholinergics, have been shown to reduce exacerbations and improve lung function and health-related quality of life among patients with moderate to severe disease (5)(6)(7). Nonetheless, use of and adherence to COPD maintenance medications remain low, ranging from 29 to 56%, and contribute to increased hospitalization, health care costs, and mortality (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%